Effects of constant kinetic energy of different impacting particles on slurry erosion wear of AA 6063 - Nandre, Bhushan D.; Desale, Girish R. (Journal of Tribology-Transactions of the ASME, 2018)
The present experimental study investigates the effect of constant kinetic energy on erosion wear of aluminum alloy 6063. Three different natural erodents (quartz, silicon carbide, and alumina) with different particle sizes are used to impact at 45 deg and 90 deg impact angles. For calculating the number of particles in the slurry pot, it is assumed that the solid particles are of spherical shape. The total numbers of impacting solid particles were kept constant by adjusting the solid concentration, velocity, and test duration. The scanning electron microscope (SEM) images of the three erodents show that the alumina particles have sharp edges with more angularity, and silicon carbide particles have subangular nature while quartz particles are blocky in shape. The mass loss per particle at 45 deg impact angle is observed higher than at normal impact angle. It may be due to the change in material removal mechanism with changing the impact angle. It is also found that the mass loss per particle from the target material having different particle size with constant kinetic energy remains constant for respective erodents. This indicates that the velocity exponent of impacting particles is around 2. The SEM images of eroded surfaces reveal the different mechanisms of material removal at 45 deg impact angle and at normal impact angle.

Study the effect of impact angle on slurry erosion wear of four different ductile materials - Nandre, Bhushan D.; Desale, Girish R. (Materials Today: Proceedings, 2018)
The test rig fabricated for the present work has an ability to study the effect of orientation angle of erosion wear. The particles of Indian Standard sand (Quartz) selected as erodent for the present investigation because it is the most widely occurs in natural slurries. Experimental investigations on erosion behavior of ductile materials AISI SS304, AA 6063, Copper and Brass have been carried out using solid-water mixtures of the above erodent. The erosion wear due to solid-liquid mixture of IS Sand and tap water at different impact angles shows typical ductile erosion behavior for the selected materials. The maximum erosion is observed at 22.5° angle for AISI SS 304, 45o for AA 6063, 22.5o for Copper and 30o for Brass. The minimum erosion is observed at 90o orientation angle for all the materials. The eroded specimens were examined under the Scanning Electron Microscope (SEM) at minimum and maximum wear orientation angles. The SEM micrographs of eroded specimens depict the mechanism of material removal.
Keywords: AA 6063; AISI SS304; brass; Copper; Quart; SEM; Slurry erosion